Adopting BEPS Inclusive Framework in Indonesia:Taxation Issues and Challenges in a Digital Era - Tambunan, Maria R.U.D (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2020)
This research is intended to discuss the new framework of taxing a highly digitalized economy, known as Base Erosion and Profit Shifting (BEPS) Inclusive Framework. This research discusses challenges that will be faced by Indonesia while adopting that new framework into domestic jurisdiction despite its potential benefit for state revenue. Taxing a highly digitalized economy under the physical-presence concept has been considered obsolete and tends to encourage Multinational Enterprises to shift their profit into low tax jurisdiction. This research applies a qualitative approach and research method. The data collection was done through a literature review and expert interviews. Organization for Economic Cooperation and Development (OECD), with the support of G20 members, proposes the solution based on global consensus. The solution is to establish a nexus to allocate taxing rights and profit allocation to the market jurisdiction. Indonesia has formulated a domestic legal basis despite myriad challenges. The challenges include coverage of the establishment of technical legal implementing guidelines and the improvement of the tax authority to optimize its performance. Essentially, this study highlights the legislation and organizational capacity of the Indonesian context. The study finds the ability to establish the technical regulation is seems questionable and similarly to the organization's capability to implement the project.